Complex and contradictory: The doing of gender on regional development boards - Sheridan, A.; McKenzie, Fiona Haslam; Still, L. (Wiley-Blackwell, 2011)
Recognizing gender as a social construction, in this article we explore the complex, and in many ways contradictory, 'doing' of gender on regional development boards in Australia. While the number of women on these boards has risen over the past decade, the overwhelming sense on these ministerially appointed boards are awarded institutional privilege. Their roles provide them with status and benefits and their membership postitions provide them with status and benefits and their membership positions them as leaders within the (masculine) hegemony. This space is not, however, uniformly masculinized. With the limited resources at their disposal and little public recognition of their roles, the boards have limited agency. These poorly resourced boards are populated by women and men board members, while vested with important titles, are relatively powerless and are expected to undertake duties and display behaviour that is more consistent with a feminized role. The doing of gender can also be seen in the primacy of the economic over the social in regional development, where the economic is strongly associated with creating employment, especially in industries where men have traditionally dominated, rather than in the more feminized domains of services. This doing of gender points to the persistence of conservative gender patterns reinforcing a masculinized model of business. The contradiction here is that while they subscribe to this masculinized model, they are unable to deliver on outcomes because they do not have direct control over resources.